Analysis of the 677 C→T Mutation of the Methylenetetrahydrofolate Reductase Gene in Different Ethnic Groups - Franco, R. F.; Araújo, A. G.; Guerreiro, J. F.; Elion, J.; Zago, M. A. (Thrombosis and Haemostasis, 1998)
A recently described mutation in the methylenetetrahydrofolate reductase (MTHFR) gene (a C to T transition at nucleotide 677) is associated with a thermolabile phenotype and decreased enzyme activity. In homozygotes, the mutation is also related to hyperhomocysteinemia and increased risk for atherosclerotic disease and (apparently) venous thrombosis. The prevalence of this mutation in different human populations is unknown. We have investigated the frequency of the 677 C→T mutation in the MTHFR gene in 337 individuals (674 chromosomes) belonging to four ethnic groups: Whites, African and Brazilian Blacks, Asians and Amerindians. The frequencies of the positive allele among Whites and Asians were similar to those previously reported for Caucasian populations. The positive allele seems to be slightly rarer among the Amerindians (frequency 24.0%) in comparison to Whites and Asians, with a heterogeneous distribution among the five Indian tribes analysed. In contrast, the mutation has a very low prevalence in Blacks, especially among the African Blacks, for whom the mutation was absent in homozygosity. Our data indicate that the 677 C→T MTHFR mutation has a significantly heterogeneous distribution among different ethnic groups, a fact that may contribute to explain geographical or racial differences in the risk for vascular disease.